Management of the Pediatric Neurocritical Care Patient - Horvat, Christopher M.; Mtaweh, Haifa; Bell, Michael J. (Seminars in Neurology, 2016)
Pediatric neurocritical care is a growing subspecialty of pediatric intensive care that focuses on the management of acute neurological diseases in children. A brief history of the field of pediatric neurocritical care is provided. Neuromonitoring strategies for children are reviewed. Management of major categories of acute childhood central neurologic diseases are reviewed, including treatment of diseases associated with intracranial hypertension, seizures and status epilepticus, stroke, central nervous system infection and inflammation, and hypoxic-ischemic injury.
Keywords: traumatic brain injury; neurocritical care; neuromonitoring; pediatric stroke; status epilepticus; neurologic emergencies